Does Green Innovation Matter? A Study On Indonesia's SMEs - Setyo Ferry Wibowo, Gatot Nazir Ahmad, Achmad Fauzi (Jurnal Manajemen, 2019)
This study examines the effect of green innovation on competitive advantage and company performance. A Survey of 200 top managers and owners of SMEs in Indonesia was conducted to gather the data. Structural Equation model was used to examine the measurement model and the structural model. The hypotheses test results state that green innovation has a positive effect on competitive advantages and competitive advantages influence the company’s non-green performance. However, green innovation and green competitive advantage have not proven to influence the company's green performance. Also, green performance has not been proven to affect non-green performance. This study contributes academically to the development of green innovation and company performance literature in the context of SMEs in developing countries, which is under-researched.